PENERAPAN METODE INQUIRY UNTUK MENGURANGI KESALAHAN SISWA DALAM MENYELESAIKAN SOAL PADA MATERI ARITMATIKA SOSIAL KELAS VII B SEMESTER GANJIL SMPN 1 SUKOWONO TAHUN AJARAN 2012/2013 - Mahendra, Novita Cahya; Dafik, D; Setiawan, Toto’ Bara (KadikmA, 2012)
Abstract. Inquiry method is a discovery learning method where the students are given a problem or a unique phenomenon in such away the students can solve the problem. This method is also suitable to reduce the studentâs mistake in solving problem of social arithmetic topic. The research subject is VII B students of SMPN 1 Sukowono. The data collection method used in this research is interview, observation, test and documentation. Theresearch observed the activity of the students and the teachers. The result shows that the activity of the students and the teachers are significantly increasing. We can conclude that the inquiry method can reduce the studentâs mistake in solving problem of social aritmetic topic. Key Words : Inquiry, studentâs mistake, social arithmetic.